The definitive guide to Django : Web development done right - Holovaty, Adrian; Kaplan-Moss, Jacob; Gilmore, Jason (Berkeley, Calif. : Apress ; New York : Distributed by Springer-Verlag, 2008)
Provides information on using the Python-based framework to create Web sites.
Includes index.
Keywords: Web sites -- Authoring programs; Python (Computer program language); Web sites -- Design; Python (Computer language)